Pengaruh Inovasi Layanan, Kompetensi Pegawai dan Komunikasi terhadap Kualitas Pelayanan di Unit Pengelola Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kelurahan Kayu Manis - Wilmarahma Sari Sitompul; Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to evaluate the extent to which service innovation, employee competence, and communication influence service quality at the Investment Management and Integrated One-Stop Service Unit of Kayu Manis Urban Village. The research method uses a quantitative approach through a questionnaire distributed to service recipients at the Investment Management and Integrated One-Stop Service Unit of Kayu Manis Urban Village during the period of January - September 2024. The sample determination was formulated using the Taro Yamane formula, resulting in a sample of 90 respondents. The data collected were analyzed using SPSS statistical program. The results indicate that, partially, service innovation and employee competence do not significantly influence service quality, contributing only 8.57% and 8.74%, respectively, with a 5% standard error. However, communication has a significant influence on service quality, contributing 63.70%. Simultaneously, all three variables significantly impact service quality, with an R-square value of 88.6%, indicating that service innovation, employee competence, and communication collectively account for 88.6% of the variation in service quality, while the remaining 11.4% is influenced by other factors outside the research.